PENGUJIAN ANOMALI SIZE EFFECT DI PASAR MODAL INDONESIA - Diahlestari, I Gst Ayu Dwi; Artini, Luh Gede Sri (E-Jurnal Manajemen, 2019)
The purpose of this study is to prove the existence of size effect anomaly in the Indonesian Capital Market which can be utilized for portfolio strategies. This study uses descriptive analysis and statistical analysis, namely different tests of two independent averages. The method used is by comparing the abnormal return and Sharpe index as a measure of performance from a large sized stock portfolio with a small sized stock portfolio that has been formed from stocks that consistently enter the Kompas 100 Index for the period 2012-2017. The results of the study showed that the average abnormal return and the Sharpe index of large sized stock portfolios were better than the small sized stock portfolios. The results of different tests show that the average difference is not significant, so it can be concluded that the size effect anomaly does not occur in the Indonesian Capital Market, especially in stocks listed on the Kompas 100 Index. Keywords: Size effect anomaly, large-small sized stock portfolio, abnormal return, Sharpe index